Public Value Penggunaan Sistem Informasi Program Layanan Masyarakat Dalam Pelaporan Kinerja Modin di Kota Surabaya - Alifia Reza Rosita; Affah Siti Rahmasari; Aqsya Adibhakti (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2026)
Digital transformation in public services is carried out to improve the effectiveness, transparency, and accountability of government services. The Surabaya City Government developed the Sistem Informasi Program Layanan Masyarakat (SIMPROLAMAS) as a digital-based reporting system for modin performance. This study aims to analyze the Public Value of SIMPROLAMAS implementation in modin performance reporting in Surabaya City using Mark Moore’s Public Value theory through the dimensions of legitimacy and support, operational capacity, and substantive value. This study used a qualitative descriptive method with data collection through interviews, observations, and documentation. The results showed that SIMPROLAMAS has formal legitimacy through SPBE and public service regulations and is supported by coordination among government agencies. In the operational capacity dimension, the implementation is supported by SOPs, training, and user assistance, although some modin still experience difficulties in adapting to digital technology. In the substantive value dimension, SIMPROLAMAS provides public value through administrative efficiency, ease of reporting, transparency, and more effective monitoring of modin performance. However, the application did not significantly increase the number of reports because modin had already reported activities manually before digitalization. Therefore, the public value is more visible in improving the quality of administrative service processes.